THE RATING AGENCIES IN THE INTERNATIONAL POLITICAL ECONOMY - Aggelos KOTIOS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2012)
The internationalization of the economy, the integration of national markets for goods, services and capital, the internationalization of production and generally augmentation of international movement of factors of production and the growing economic interdependence in recent decades have caused a rapid increase in the construction and use of indicators for assessing countries. Typically the comparative evaluation of countries is conducting, using simple or complex indicators, based on quantitative and / or qualitative variables. The results of comparative evaluation of counties usually concern the policy makers, markets and public opinion. The concentration of information in an index seems to have a practical significance and facilitate comparison between countries. From the position that a country conceives in the list of evaluation has certain economic and political implications. The different evaluation systems (indicators) of countries have however advantages and disadvantages. Many organizations for example publish indicators for the competitiveness of countries. Widely known indicators are competitiveness of World Economic Forum (WEF, Geneva) and the Institute for Management Development (IMD, Lausanne). There are also indicators of corruption, bureaucracy and regulations, investment climate, political risks and security risks. Agencies and organizations like the World Bank, IMF, EU and the OECD publish indicators often for a number of specific issues. The indicators and assessment methods of countries are often the basis for empirical economic research, data useful for counseling policy and guide action. For governments evaluation of countries is an important form of information. The advantage is that the indicators reflect complex relationships of world economy. The advantage is at the same time the disadvantage. And this is because they provide only general information. The aim of this article is to evaluate the importance of rating agencies to the configuration of world economy. For this reason, we will study the historical development of rating agencies and the causes of this development. The article also examines the issue of interest conflict and the potential impacts to state economies. Finally, it is examined the impact of rating agencies to international economic crisis.